Dumb-Bell Shaped Hydatid Cyst in the Parotid Gland – A Rare Presentation (TAJ: Journal of Teachers Association, 2018)
Human echinococcosis is a zoonotic infection caused by the tapeworm of the genus Echinococcus and transmitted by dog and other canine animals. It is a serious problem in tropical areas and is seen in many parts of Bangladesh. In children lungs are the most common site of infection, whereas in adults liver is infected most frequently. Primary hydatid cyst of the parotid gland is extremely rare, even in the endemic areas and very few cases are reported in parotid gland The disease is prevalent in most part of the world, though it is most extensive in the sheep and cattle raising areas. FNAC is contraindicated in suspected hydatid cyst cases due to risk of hypersensitivity reaction and additional precaution of intact cyst excision is mandatory in such cases to prevent recurrence and anaphylaxis reaction. A 30 year old female patient presented with gradually increasing painless large smooth cystic swelling of the right parotid region with trismus. CT scan showed a huge dumb bell shaped cystic lesion in the superficial and deep lobe of the parotid gland that is compatible with hydatid cyst. The parotid tumor was surgically removed by midline mandibulotomy approach. Pathological study of the cystic lesion confirmed hydatid disease of the parotid gland.TAJ 2017; 30(1): 73-77